Analisis Pengaruh Kompensasi, Beban Kerja terhadap Turnover Intention - Murti, Anisa Dwi; Sheviyani, Hafivah; Desiree, Hany Sekar (As-Syirkah: Islamic Economic & Financial Journal, 2023)
This study aims to analyze how compensation and workload affect turnover intention. The purpose of this research is that compensation and workload have an effect on employee performance and the effect of satisfaction on turnover intention in one of the companies in the Cikarang area, Bekasi Regency. The best human resource management, human resource management that runs all implementation systems that are directly related to human resources. The company requires employees to be prosperous to create equal benefits for both parties. And the analytical method used is the quantitative method, with the type of survey and data collection through questionnaires. This analysis is used to test the validity, reliability and multiple linear regression. The sample used was 32 people for the research sample.